Sago enterprise / Hanani Omar... [et al.] - Omar, Hanani; AK Mohiddin, DK Norhajijah; Haris, Norharizah Wati; Hussin, Elbina Nur; Mandar, Noor; Hamdani, Muhd Azmi (Faculty of Plantation & Agrotechnology, 2009)
SAGO ENTERPRISE is a business that focuses on producing products based from the sago palm (Metroxylon sp.). Our products are sago flour and Tebalui and had certificated from Sabah Forestry Department. All of these products are high demand especially in northern Sabah because it is highly used on a tourism sector. Unfortunately, the producers of sago products is very limited suppliers and about only 3 suppliers around Sabah. For the reason, we produce sago products to local people and small holders. According to the Sabah's history (early 1940), sago has saving many of people around Kuala Penyu and Beaufort on Japanese colonization. At that moment, the local people don't have any source of food especially rice because all of food sources has been taken by Japanese soldiers. Nowadays, the sago palm became as a commercial plant that can give better profit for those who involve with these plant. This is because only several areas in our country get benefit from it. As we know, sago is also has a potential to be a substitute product for substituting the starch flour.